Understanding pro-environmental behavior and improving social network research methods to inform conservation management - Clements, Kaylin Renee, author; Solomon, Jennifer N., advisor; Cross, Jennifer E., committee member; Niemiec, Rebecca M., committee member; McCarty, Christopher, committee member (Colorado State University. Libraries, 2022)
Conservation issues exist in the context of social-ecological systems, with human activities driving threats to species, habitats, and important ecosystem functions. The successes and failures of conservation efforts depend on how humans behave. Likewise, human behavior is crucial to rectifying these problems. Understanding why humans behave in ways that help or hinder conservation efforts is vital to effectively manage and prevent threats to natural resources, such as invasive species. Research specific to each social-ecological context on how social networks, knowledge, and other cultural and social psychological factors influence behavior is needed to inform management decisions. In addition, effective and efficient social science methods are needed for practitioners to assess relevant behaviors more easily. This dissertation contributes evidence that advances our understanding of pro-environmental behaviors that help control invasive lionfish (Pterois volitans) in Belize and Florida and provides insights into data collection methods on social networks. Each manuscript assesses factors that influence a specific target behavior. The first manuscript (Chapter 2) explores what factors affect consumption of the venomous, but edible, invasive lionfish in Belize. To determine the viability of a lionfish market in Belize, a national study of Belizeans (n = 400) and foreign tourists (n = 400) was implemented using structured surveys that assessed consumers' willingness to try lionfish, knowledge about lionfish, attitudes toward purchasing lionfish, and fear of trying new foods, or food neophobia. Findings show that most Belizeans and foreign tourists are willing to eat lionfish given the opportunity, but that a misperception that lionfish is not safe to eat and availability are barriers to eating lionfish. Belizeans, though concerned about lionfish, are less willing to consume lionfish than tourists and more likely to believe lionfish are unsafe to eat. In addition, when asked why they would not eat lionfish, the most common reasons Belizeans described were related to perceived danger or preference. These and other findings about consumer behavior toward seafood in Belize, such as that Belizeans primarily choose to eat seafood for health reasons and prefer snapper to other types of seafood, provide important insights into opportunities to grow demand for lionfish and decrease barriers related to risk perceptions. The second manuscript (Chapter 3) shares findings from a mixed methods study to understand how motivation and social capital affect removal of lionfish in Florida by spearfishers who hunt lionfish, or lionfish hunters. Findings are shared from semi-structured interviews (N = 75) as well as an online structured survey of 186 lionfish hunters. Results show that lionfish hunters who are motivated by money kill more lionfish than those motivated by other reasons. However, this group is very small in number and is sensitive to decreased lionfish numbers because it is prohibitive to commercial spearfishers' ability to profit from them. In addition, lionfish hunters who have a social contact who helps them sell lionfish kill more lionfish. However, this is still a small group. Most lionfish hunters in Florida are motivated to kill lionfish to protect Florida's reefs, to eat lionfish, and because it's fun. In addition, most feel an obligation or duty to kill lionfish in order to protect the reefs. Effective management strategies, therefore, should engage lionfish hunters across motivations to maintain consistent and long-term control of the population. In addition, practitioners should continue to cultivate a community around lionfish removal to better support money-motivated lionfish hunters' efforts to sell lionfish. The third manuscript (Chapter 4) investigates the efficacy of including an example social network map in an online structured survey to increase responses to questions about social network contacts. Social network research can be inhibited by willingness of respondents to provide names and contact information of themselves and their acquaintances. For social network research to be more feasible among practitioners in the conservation field and beyond, effective methods for collecting this type of information are essential. This experimental study compared responses (N = 186) to social network questions between those who completed a survey with an example social network map versus a survey without a map. Results show that the example map did not increase provision of network contacts and did not influence the types of ties reported. Therefore, while a map may not help in collecting more data, if it is necessary to include for explanatory purposes in a social network survey, it likely will not bias responses. Resistance among respondents to providing this information in this study demonstrate the need for further exploration into effective social network data collection methods for large groups, especially when snowball sampling is necessary.
Keywords: invasive species; pro-environmental behavior; coupled human-natural systems; social network analysis; lionfish